2001
DOI: 10.1002/glia.1034
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the neural RNA‐binding protein Musashi1 in human gliomas

Abstract: Tumor cells arising from a particular tissue may exhibit the same gene expression patterns as their precursor cells. To test this proposition, we have analyzed the expression of a neural RNA-binding protein, Musashi1, in primary human central nervous system (CNS) tumors. In rodents, Musashi1 is expressed predominantly in proliferating multipotent neural precursor cells, but not in newly generated postmitotic neurons. The expression of Musashi1 is downregulated with the successive progression of neurogenesis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
137
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(143 citation statements)
references
References 34 publications
6
137
0
Order By: Relevance
“…32) Musashi 1 containing two ribonucleoprotein (RNP)-type RNA-binding domains (RBDs) is also overexpressed in malignant gliomas. 40) These results suggest that various types of RNA-binding proteins are involved in cell proliferation, and expression alterations of those RNA-binding proteins often cause tumor formation. This prompted us to examine the expression of Hqk in human tumors.…”
Section: Discussionmentioning
confidence: 92%
“…32) Musashi 1 containing two ribonucleoprotein (RNP)-type RNA-binding domains (RBDs) is also overexpressed in malignant gliomas. 40) These results suggest that various types of RNA-binding proteins are involved in cell proliferation, and expression alterations of those RNA-binding proteins often cause tumor formation. This prompted us to examine the expression of Hqk in human tumors.…”
Section: Discussionmentioning
confidence: 92%
“…26 Here we describe an elevated ENPP1 expression in GSCs compared with normal brain extracts and fNSCs. E-NPP1-deficient GSCs are characterised by downregulation of known stem cell markers, such as CD133, LHX2, MSI1, LGR5 and CD15, 4,8,9,34,35 as well as an overall downregulation of stem cell-associated genes as seen by comparison with published stem cell gene signatures. 24,25 Moreover, GFAP and S100 beta, differentiation marker delineating the astrocytic cell lineage, are upregulated upon knockdown of ENPP1 in cultured GSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma stem-like cells (GSCs) share properties with neural precursor cells, such as a capacity for self-renewal, differentiation and maintained proliferation, as well as stem cell marker expression. 4,5,8,9 GSCs were originally defined by expression of CD133 (Prominin-1) and its extracellular AC133 epitope. 4 Although recent studies have shown that GSCs are not entirely restricted to the CD133-positive cell population, 10,11 there is a large body of evidence linking enhanced CD133 expression to poor prognosis in glioblastoma.…”
mentioning
confidence: 99%
“…The role of neural stem cells and multipotential progenitors as cell-of-origin of glioblastoma has been suggested by the detection of positive immunoreactivity for immature markers such as nestin in human tumors (Dahlstrand et al, 1992;Toda et al, 2001;Ignatova et al, 2002;Bouvier et al, 2003) and by studies in transgenic mice overexpressing activated Ras and Akt in nestin ϩ cells (Holland, 2000). et al, 2004), its mutation is observed in sphere-forming cells isolated from human glioblastoma (Ignatova et al, 2002) and its expression in the adult brain is confined to germinal areas (van Lookeren Campagne and Gill, 1998), we postulated that characterization of the changes induced by loss of p53 in cells of the adult SVZ could lead us to a better understanding of the genesis of glial tumors.…”
Section: Discussionmentioning
confidence: 99%